A Numerical Study on the Implications of Subgrade Reinforcement with Geosynthetics in Pavement Design. (2016) - Neves, José; Lima, Helena; Gonçalves, Margarida
Abstract: The main purpose of this paper is to present a numerical study to demonstrate the implications of subgrade reinforcement with geosynthetics in road pavement design. A parametric analysis was carried out with the finite element program ADINA using two-dimensional modeling. This analysis considered different pavement materials and structures, traffic conditions and subgrade soil quality. The pavement reinforcement effect was analyzed in terms of fatigue and rutting design criteria. Overall, the results of numerical modeling confirmed the reinforcement effect and pointed out the most important factors influencing the use of geosynthetics at the subgrade level for this purpose.